Análisis y diseño de la red FTTH para la urbanización privada Jardines de Amagasí - Andagoya Guerrero, Roberto Lenin (2017)
User demand and technological advances have driven the evolution of communications networks by requiring Internet providers to offer networks capable of providing telephony, data and television services by the same with bandwidth in the order of the Tera Hertz, in other words, convergent networks capable of giving the user the ability to use applications and services in real time. The urbanization Jardines de Amagasí has the following problems as they are that the bandwidth is very little for the current services, and being deployed through the telephone network produces delays, especially on the surveillance network and video services. For this reason, this degree work tries to establish the technical and economic parameters for the design of a fiber optic network to the home (FTTH) for the Jardines de Amagasí Urbanization, which can support voice, data and television, which is created considering the rules of the CNT EP (National Corporation of Telecommunications Public Company). An analysis of the current network of the urbanization is made through measurements of bandwidth, Jitter and availability, also economic viability is determined through the VAN and TIR indicators. Concluing that the design is technically feasible with an increase of the bandwidth of more than two times and economically feasible with a recovery of the invested capital in a year.